Дослідження впливу виробництва сільськогосподарської продукції на екологічний стан водних ресурсів - Троїцька, О. О.; Ткаліч, І. О.; Бакарджиєв, Роман Олександрович; Бакарджиев, Роман Александрович; Bakardzhyiev, Roman; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia (My University, 2020)
UK: В статті сформульовано актуальність проведених досліджень, яка обумовлена тим, що в даний час основними джерелами забруднення води в багатьох країнах є не промисловість, а сільське господарство, оскільки найпоширенішими хімічними забруднювачами є сільськогосподарські нітрати. Проведений аналіз фондових даних, дозволив визначити значення середньорічних та найгірших показників вмісту азоту нітратного у воді I підйому з ДВС-1, ДВС-2 і ОВС ПАТ «Запоріжсталь» за 20152019 рр. Визначено клас і категорію якості дослідних вод. За середньорічними величинами вони характеризуються як «погані», за ступенем чистоти як «брудні», а за найгіршими, як «дуже погані» і «дуже брудні». Отже, показники вмісту азоту нітратного в дослідних пробах води (2015-2019 рр.), були аналогічними, що підтверджує погіршення якості води р. Дніпро в межах м. Запоріжжя. Зважаючи на інтенсифікацію сільського господарства, важливо посилити контроль за вмістом нітратів з метою покращення екологічного стану водних ресурсів р. Дніпро і забезпечення екологічної безпеки та здоров’я населення. RU: В статье сформулирована актуальность проведенных исследований, которая обусловлена тем, что в настоящее время, основными источниками загрязнения воды является сельское хозяйство, поскольку наиболее распространенными химическими загрязнителями являются сельскохозяйственные нитраты. Анализ фондовых данных, позволил определить значение среднегодовых и худших показателей содержания азота нитратного в воде I подъема с ДВС-1, ДВС-2 и ОВС «Запорожсталь» за 2015-2019 гг. Определен класс и категория качества исследуемых вод. По среднегодовым величинами они характеризуются как «плохие», по степени чистоты как «грязные», а по худшим, как «очень плохие» и «очень грязные». Таким образом, показатели содержания азота нитратного в исследуемых пробах воды (2015-2019 гг.), были аналогичными, что подтверждает снижение качества воды р. Днепр в пределах г. Запорожья. Несмотря на интенсификацию сельского хозяйства, важно усилить контроль за содержанием нитратов в целях улучшения экологического состояния водных ресурсов р. Днепр и обеспечения здоровья населения. EN: According to a Global survey of water pollution by agriculture FAO and the International water management Institute, at present, the main sources of water pollution in many countries are no cities or industry, and agriculture, as the most common chemical pollutants worldwide, are agricultural nitrates. According to expert estimates, the share of nitrates from agricultural sources ranges from 30 to 90% of the total nutrient pollution of water. Water contaminated with nitrate poses a serious risks to human health and ecosystems of the planet. Therefore, environmental monitoring of surface water quality of the Dnieper river based on the analysis and performance assessment of nitrate levels is important. The values of nitrate can be used as indicators to measure the process of surface water pollution, including agricultural runoff. The analysis of stock laboratory data allowed to determine the values of average and maximum (worst) indicators in the content of nitrate nitrogen in the water I rise with DVS-1, DVS-2 and OVD JSC "Zaporizhstal" for the period 2015-2019. Based on the comparison of average and maximum (worst) values of the studied index determined the class and category of water quality I upgrade with DVS-1, DVS-2 and OVD JSC "Zaporizhstal". Quality research water annual average characterized the condition as "poor" according to the degree of purity as "dirty", the maximum (worst) indicators - as "very bad", according to their degree of purity "very dirty". Consequently, the concentrations of nitrate nitrogen in the experimental water samples as annual average and maximum (worst) values for the fiveyear study period, was similar, which confirms the deterioration of water quality. The Dnieper river within the city of Zaporozhye. Despite the intensification of agricultural production in Ukraine, it is important to strengthen the monitoring of nitrate content with the aim of improving the ecological status of water resources in the Dnieper and environmental safety and health.
Исследование влияния производства сельскохозяйственной продукции на экологическое состояние водных ресурсов
Study of the influence of agricultural production on the ecological state of water resources
Keywords: вміст нітратів; екологічний контроль; клас і категорія якості; якість поверхневих вод; содержание нитратов; экологический контроль; класс и категория качества; качество поверхностных вод; nitrate content; environmental control; quality class and category; surface water quality